Monitoring mitochondrial translation in living cells. (15th February 2021) - Yousefi, Roya; Fornasiero, Eugenio F; Cyganek, Lukas; Montoya, Julio; Jakobs, Stefan; Rizzoli, Silvio O; Rehling, Peter; Pacheu‐Grau, David
Abstract: Mitochondria possess a small genome that codes for core subunits of the oxidative phosphorylation system and whose expression is essential for energy production. Information on the regulation and spatial organization of mitochondrial gene expression in the cellular context has been difficult to obtain. Here we devise an imaging approach to analyze mitochondrial translation within the context of single cells, by following the incorporation of clickable non‐canonical amino acids. We apply this method to multiple cell types, including specialized cells such as cardiomyocytes and neurons, and monitor with spatial resolution mitochondrial translation in axons and dendrites. We also show that translation imaging allows to monitor mitochondrial protein expression in patient fibroblasts. Approaching mitochondrial translation with click chemistry opens new avenues to understand how mitochondrial biogenesis is integrated into the cellular context and can be used to assess mitochondrial gene expression in mitochondrial diseases. Synopsis: This study monitors mitochondrial protein synthesis with spatial resolution in single cells of multiple cell types. Labelling of mitochondrial translation products allows to monitor translation with spatial resolution within single cells. Mitochondria show different levels of protein synthesis within a single cell. Protein synthesis occurs in mitochondria of the pre‐ and the postsynapse. Abstract : This study monitors mitochondrial protein synthesis with spatial resolution in single cells of multiple cell types.